POTRET RADIKALISASI GERAKAN KEAGAMAAN (Studi Kasus Organisasi GARDAH di Kota Cirebon, Jawa Barat) (Harmoni, 2014)
In Indonesia today, Islamic religious movements with radical tendencies have emerged across the country. This paper uses qualitative methods to study the Pagar Aqidah (GARDAH) or the Aqidah Protector organization in Cirebon, a movement that has sought to address issues of apostasy, gambling, the distribution of liquor, and heresy. This study shows that GARDAH is an organization based on the Quran and the Hadith and positions itself as the protector and soldier of the people in the face of Aqidah deviation and wickedness.. In their handling of cases of apostasy, gambling, liquor distribution, and heresy, GARDAH has collaborated with other organizationsΓÇöparticularly Almanar (Aliansi Masyarakat Nahi Munkar/Community Alliance of Wickedness Prevention). Due to their actions in cases of apostasy, some members of GARDAH are now facing legal charges. On the other hand, their attempts to address liquor distribution has led to the closure of liquor distributors. Their actions were further strengthened by the passing of a law that prohibited alcohol in the area by the mayor.
Keywords: Goverment; Islamic Sharia; Religious Movement; Radikalisasi; Pemerintah; Syariat Islam; Gerakan Keagamaan